2000
DOI: 10.1073/pnas.97.7.3479
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β 1 hyperexpression in African-American hypertensives: A novel mediator of hypertension and/or target organ damage

Abstract: Hypertension, a remediable risk factor for stroke, cardiovascular disease, and renal failure, affects 50 million individuals in the United States alone. African Americans (blacks) have a higher incidence and prevalence of hypertension and hypertension-associated target organ damage compared with Caucasian Americans (whites). Herein, we explored the hypotheses that transforming growth factor-beta(1) (TGF-beta(1)) is hyperexpressed in hypertensives compared with normotensives and that TGF-beta(1) overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 47 publications
2
61
0
Order By: Relevance
“…Overproduction of TGF␤1 has been experimentally linked to the sequela of chronic hypertension, including vascular remodelling and progressive renal disease. 11,22 Moreover experimental data have also demonstrated that high circulating levels of this cytokine can mediate organ and tissue damage. 23,24 The exact mechanism by which TGF␤1 activity is enhanced in hypertensive renal disease is not yet clear, but an overproduction of TGF␤1 has been reported to be mediated by angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overproduction of TGF␤1 has been experimentally linked to the sequela of chronic hypertension, including vascular remodelling and progressive renal disease. 11,22 Moreover experimental data have also demonstrated that high circulating levels of this cytokine can mediate organ and tissue damage. 23,24 The exact mechanism by which TGF␤1 activity is enhanced in hypertensive renal disease is not yet clear, but an overproduction of TGF␤1 has been reported to be mediated by angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…The biological actions of TGF␤1 and the reported association with renal pathology support the hypothesis that increased frequency of TGF␤1-overproduction is a candidate mechanism for progression of hypertensive renal disease to end-stage renal disease. 11 In view of this, it has been recently reported that some antihypertensive drugs such as angiotensinconverting enzyme (ACE) inhibitors decrease TGF␤1 levels, and that changes in TGF␤1 values may predict the course of diabetes nephropathy. 27 Accordingly, it should be possible to select a subset of hypertensive subjects (with higher levels of TGF␤1) who are more responsive to the treatment and characterised by a possible slow progression of renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The codon 10 is an important site for the regulation of TGF-β1 gene expression and the C allele at this site was reported to be linked to high levels of TGF-β1 mRNA and its protein. 19,20 In fact, Suthanthiran et al reported that both mRNA and protein levels of TGF-β1 in the population were higher among subjects genotyped as C/C or C/T at codon 10 compared with those genotyped as T/T. 19 Thus, the polymorphism causing an amino acid substitution from leucine to proline might influence TGF-β1 protein secretion, which up-regulates its own transcription via AP-1 sites located in its promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The +869T/C gene polymorphism was located in exon 1 and encoded the signal peptide of TGFB1 which was indispensable to the secretion and translation of proteins. The +869T/C transition caused a leucine to proline substitution which likely increased the secretion rates of TGFB1 by influencing the transcription and expression of TGFB1 gene (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%